Implementasi Kebijakan Sekolah Ramah Anak untuk Mencegah Bullying pada Siswa ADHD di SD Inklusif - Khairunnisa, Rizka; Muttaqin, Muhammad Fauzan (CV. SINAR HOWUHOWU, 2025)
This study examines the implementation of Child-Friendly Schools (SRA) policies in preventing bullying of students with Attention Deficit Hyperactivity Disorder (ADHD) in inclusive elementary schools. The main focus of the research is how SRA principles are applied to create a safe, inclusive, and supportive learning environment for students with special needs. Using a descriptive qualitative approach, this study examines the role of teachers, school policies, and intervention strategies designed to build an anti-bullying culture. Data was obtained through literature studies and field observations, then analyzed using content analysis techniques. The results of the study show that comprehensive assessment, curriculum modification, and support of special assistant teachers are key factors in the success of inclusive education. The consistent and collaborative implementation of SRA policies has been proven to increase the awareness of all school residents on the importance of protecting and accepting student diversity. In addition, the involvement of teachers, parents, and sustainable government policies is indispensable to strengthen inclusive education systems. This study emphasizes that the implementation of SRA is not only a bullying prevention strategy, but also a strategic step in ensuring the right of children with special needs to obtain equal, quality, and development-oriented education that is oriented towards the development of potential and positive character.